Tradition and Innovation: Baptismal Rite and Mystagogy in Theodore of Mopsuestia and Narsai of Nisibis. - Nathan Witkamp (Vigiliae Christianae, Supplements, 2018)
In Tradition and Innovation , Nathan Witkamp convincingly argues that Narsai of Nisibis' (d. circa 503) baptismal rite and mystagogy, as portrayed in his Liturgical Homilies 21-22, are much less dependent on Theodore of Mopsuestia (ca. 350-ca. 428) than scholars have previously supposed. Narsai's baptismal rite turns out to represent a particular East Syrian liturgical tradition, independent of Theodore. In his mystagogy, Narsai uses Theodore's Baptismal Homilies 1-3 as just one source among others to create the artwork he desires. This detailed comparative study contributes to our understanding of rite and mystagogy in Theodore and Narsai within the broader early Syrian context, as well as to the reception of Theodore by Narsai and the East Syrian Church.